Doing Math With Python. (October 2015) - Unknown
Abstract : Python is now arguably the most popular programming language for penetration testers, security researchers and hackers of all stripes. It allows for rapid prototyping and quick-and-dirty scripts for solving immediate problems. But it also has a rich library and structures that support advanced development, whether your preference is for object-oriented or functional programming.